Propriedades mecânicas e de corrosão de dois aços inoxidáveis austeníticos utilizados na fabricação de implantes ortopédicos - Giordani, Enrico José [UNESP]; Ferreira, Itamar; Balancin, Oscar (FapUNIFESP (SciELO), 2007)
ASTM F 138 austenitic stainless steel is extensively used as an orthopedic implant material. However, some aspects, such as low strength in the annealed condition and susceptibility to localized corrosion, limit wider use of this kind of steel. Recently, a high-nitrogen austenitic stainless steel, specified in the standard ISO 5832-9, has been indicated as an alternative to ASTM F 138 steel for more severe loading and permanent application inside the human body. In this work, microstructure, mechanical properties, corrosion resistance and fatigue behavior of both steels were determined and compared. ISO 5832-9 steel displayed better mechanical and corrosion behaviors than did ASTM F 138 steel The combination of these features lead ISO steel to enhanced fatigue performance in both neutral and aggressive environments. Analyzed were the role of nitrogen in solid solution, combined with niobium in the Z-phase, and the factors that led to superior ISO 5832-9 properties.
Mechanical properties and the corrosion of two austenitic stainless steels used in the manufacture of orthopedic implants
Keywords: Austenitic stainless steel; ISO 5832-9; Metallic biomaterials; biogenic material; corrosion; fatigue; mechanical property; microstructure; niobium; steel; strength